Determinan Kepuasan dan Loyalitas Pengguna Jasa Hotel Syariah di Jakarta (Studi Pada Sofyan Hotel Betawi) - Winarno, Slamet Heri (Universitas Medan Area, 2019)
This study aims to identify and test the factors that can affect customer satisfaction and customer loyalty, especially in hotels that apply sharia principles such as Sofyan Hotel Betawi. The subjects of this study were guests staying overnight with a sample size of 170 people who met the research criteria and requirements using a purposive sampling technique. The research design uses quantitative research survey methods, interviews and questionnaires. Data collection tools use a Likert scale as quantitative data. Quantitative data were analyzed using descriptive analysis and inferential analysis using the SEM path analysis method. The results showed that service quality and price perception had a positive and significant effect on customer satisfaction by 24.6%. Customer loyalty is influenced by factors of service quality and customer satisfaction positively and significantly by 51.9%.